Aortic biomechanics in hypertrophic cardiomyopathy - Badran, Hala Mahfouz (Glob Cardiol Sci Pract, 2015)
Background: Ventricular-vascular coupling is an important phenomenon in many cardiovascular diseases. The association between aortic mechanical dysfunction and left ventricular (LV) dysfunction is well characterized in many disease entities, but no data are available on how these changes are related in hypertrophic cardiomyopathy (HCM). Aim of the work: This study examined whether HCM alone is associated with an impaired aortic mechanical function in patients without cardiovascular risk factors and the relation of these changes, if any, to LV deformation and cardiac phenotype. Methods: 141 patients with HCM were recruited and compared to 66 age- and sex-matched healthy subjects as control group. Pulse pressure, aortic strain, stiffness and distensibility were calculated from the aortic diameters measured by M-mode echocardiography and blood pressure obtained by sphygmomanometer. Aortic wall systolic and diastolic velocities were measured using pulsed wave Doppler tissue imaging (DTI). Cardiac assessment included geometric parameters and myocardial deformation (strain and strain rate) and mechanical dyssynchrony. Results: The pulsatile change in the aortic diameter, distensibility and aortic wall systolic velocity (AWS') were significantly decreased and aortic stiffness index was increased in HCM compared to control (P < .001) In HCM AWS' was inversely correlated to age(r = − .32, P < .0001), MWT (r = − .22, P < .008), LVMI (r = − .20, P < .02), E/Ea (r = − .16, P < .03) LVOT gradient (r = − 19, P < .02) and severity of mitral regurg (r = − .18, P < .03) but not to the concealed LV deformation abnormalities or mechanical dyssynchrony. On multivariate analysis, the key determinant of aortic stiffness was LV mass index and LVOT obstruction while the role LV dysfunction in aortic stiffness is not evident in this population. Conclusion: HCM is associated with abnormal aortic mechanical properties. The severity of cardiac phenotype, not LV deformation, is interrelated to aortic stiffness in patients with HCM. The increased aortic stiffness seems to be promising module that can be added as clinical risk parameter in HCM.